The Effectiveness of Project Based Learning in Classroom Activities to Develop Skimming Skills in Improving Reading Comprehension of Descriptive Texts Among VII Grades - M. Andriana Gaffar; Paulina Novarita; Khopipah Indar Parawansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This quasi-experimental study examined the effectiveness of Project-Based Learning (PBL) in developing Grade VII students' skimming skills for descriptive text comprehension at SMPN 18 Bandung over four weeks. A total of 62 students participated in the study, divided equally into an experimental group (n=31) and a control group (n=31). Both groups were assessed using pre-test and post-test instruments. The experimental group, which received instruction through the PBL approach, showed a statistically significant improvement in their reading comprehension scores—from a pre-test average of 27.387 to a post-test average of 40.354 (gain = 12.967). In contrast, the control group, which received conventional instruction, improved from 25.354 to 36.387 (gain = 11.032). The results indicate that the PBL approach is more effective than traditional methods in enhancing students’ skimming skills and comprehension of descriptive texts. It is suggested that English teachers consider implementing Project-Based Learning as an alternative instructional strategy to improve reading comprehension and overall academic achievement.